Viscosity of liquid diethylene, triethylene and tetraethylene glycols at moderately high pressures using a vibrating wire instrument - Pereira, Marta F. V. (2018)
New viscosity measurements of compressed liquid diethylene glycol (DiEG), triethylene glycol (TriEG) and tetraethylene glycol (TeEG) have been performed using a vibrating wire instrument operated in the forced oscillation mode. The measurements have been carried out in a range of pressures up to 70 MPa and temperatures from (293 - 363) K, covering a total range of viscosities from (3.46 - 1.15 x 10^2) mPa,s. Complementary experimental density data were obtained for the same glycols using an Anton Paar vibrating U-tube densimeter. These measurements have been performed in a range of temperatures from about (283 - 363) K and at pressures up to about 70MPa. The viscosity results were correlated with density, using a modified hard-spheres scheme. The experimental density data were correlated, as a function of temperature and pressure, with a modified Tait-type equation. The expanded uncertainty of the present viscosity results at a 95% confidence level is estimated to be less than ±2.0% for viscosities up to 68 mPa s and less than ±2.6% for higher viscosities. The densities have an expanded uncertainty of ±0.2% at a 95% confidence level.